2016
DOI: 10.3130/jaabe.15.319
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Optimal Energy Consumption Measures for Building Façades with a Parametric Combination of Blinds, Lighting and HVAC Systems

Abstract: This paper investigates the indoor light environment, lighting energy consumption and total energy including annual HVAC system in temperate and temperate monsoon climate zones. In certain areas, annual temperature variation is very extreme therefore a high thermal insulating performance for glazing systems is required to minimize the effects of outdoor temperature changes on the indoor temperature.To obtain a variable solar heat gain coefficient value for annual energy performance, single and double skin faça… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several studies have considered movable sun shading devices such as roller blinds [18,19], Venetian blinds [20][21][22] and louvres [23,24]. The effect of these systems is much greater if they are outside the glazing in both energy demand [25][26][27] and thermal comfort [28], as previous research has shown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have considered movable sun shading devices such as roller blinds [18,19], Venetian blinds [20][21][22] and louvres [23,24]. The effect of these systems is much greater if they are outside the glazing in both energy demand [25][26][27] and thermal comfort [28], as previous research has shown.…”
Section: Introductionmentioning
confidence: 99%